Pengaruh Profitabilitas, Keputusan Investasi, Kebijakan Hutang, dan Market Value Added Terhadap Nilai Perusahaan pada Perusahaan Makanan dan Minuman - Enjeli Puspita Sari; Hari Setiono; Muhammad Bahril Ilmiddaviq (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to examine the influence of profitability, investment decisions, debt policy, and market value added on company value in food and beverage companies listed on the Indonesian Stock Exchange. The population used in this research is food and beverage companies listed on the Indonesia Stock Exchange (BEI) in the 2021-2023 period. Sample selection used purposive sampling, based on the purposive sampling method, 39 data were obtained from 13 samples that met the criteria with data obtained from the official website of the Indonesia Stock Exchange (www.idx.co.id). The data analysis technique uses multiple linear regression analysis with SPSS (Statistical Product and Service Solutions) tools. The research results show that profitability, investment decisions, debt policy, and market value added have a positive and significant effect on company value.